(Re)examining the effects of open classroom climate on the critical consciousness of preadolescent and adolescent youth. Issue 3 (3rd July 2022) - Rapa, Luke J.; Bolding, Candice W.; Jamil, Faiza M.
Abstract: An open classroom climate, one where diverse opinions and discussion of social and political issues are welcome, promotes civic development among youth and fosters critical consciousness. Critical consciousness, defined as the capacity to recognize societal inequity along with the motivation and action taken to challenge such inequity and promote positive social change, also engenders civic development and engagement. Advancements in critical consciousness measurement and changes in the sociopolitical climate over the past two decades suggest the need to reexamine the effects of open classroom climate on critical consciousness. This paper explores the extent to which an open classroom climate is associated with critical consciousness in a contemporary, diverse sample of preadolescent and adolescent youth ( n  = 4, 901, Mage = 14.69). Results suggest open classroom climate is linked with the reflection, motivation, and action dimensions of critical consciousness. Implications for promoting an open classroom climate and critical consciousness are discussed.